2014
DOI: 10.3892/ol.2014.2148
|View full text |Cite
|
Sign up to set email alerts
|

Latent infection of human cytomegalovirus is associated with the development of gastric cancer

Abstract: The worldwide contagion, human cytomegalovirus (HCMV), may cause a series of disorders in infected individuals. The aim of the present study was to investigate whether HCMV infection is associated with the development of gastric cancer. In this study, the positive expression of unique long (UL)133-UL138 and immediate-early (IE)1 genes, which are associated with viral latency and replication, respectively, were detected using nested polymerase chain reaction. A χ2 test and logistic regression analysis were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…On one hand, HCMV infection can promote tumor development (Mossman et al 2013;Teo et al 2017), whereas, on the other hand, some reports also indicated that HCMV infection can inhibit the transformation process in cancer cells (Oberstein and Shenk 2017;Kumar et al 2016). Our group previously confirmed that HCMV infection is associated with the development of GC Jin et al 2014), but the mechanism underlying its effect on the occurrence and development of GC is still not clear.…”
Section: Introductionmentioning
confidence: 91%
“…On one hand, HCMV infection can promote tumor development (Mossman et al 2013;Teo et al 2017), whereas, on the other hand, some reports also indicated that HCMV infection can inhibit the transformation process in cancer cells (Oberstein and Shenk 2017;Kumar et al 2016). Our group previously confirmed that HCMV infection is associated with the development of GC Jin et al 2014), but the mechanism underlying its effect on the occurrence and development of GC is still not clear.…”
Section: Introductionmentioning
confidence: 91%
“…3 is probably a gross underestimate. This will be especially so at ages 70+, where clinicians will assume that the illness is due to 'age' or 'an infection' [1] The work of others suggests that the role of CMV as an oncomodulatory and as oncogenic agent in certain cancers (breast ductal, gliomas, salivary duct, gastric, colon, prostate, cutaneous T-cell lymphomas and perhaps others) should be added to this list [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88]. The evidence that CMV is associated with increased risk of death for the above conditions will now be investigated.…”
Section: Operates At Multiple Levelsmentioning
confidence: 99%
“…There is now increasing evidence that latent infection with CMV is associated with a wide range of cancers [see section 5.6]. In the CMV genome the UL133-UL138 locus appears involved in a link between latent infection and gastric cancer [80]. Latent infection with CMV (in the presence of EBV) resulting in high levels of CMV IgG is associated with at least two types of cutaneous T-cell lymphoma [79].…”
Section: Sleepless Latencymentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the risk of infection with other opportunistic gastric pathogens could increase after HCMVinduced host immune modulations. Indeed, latent HCMV infection can be reactivated following immune suppression and bacterial co-infections [9,10], which may be related to development of de novo gastric cancer [11,12]. Most studies have been focused on the HCMV prevalence and associated risk factors in colorectal and lower GI tract diseases, while there is limited data on the incidence of HCMV infection in the GI tract.…”
Section: Introductionmentioning
confidence: 99%